The effectiveness of key word method in acquisition in acquisition of Arabic vocabulary: an experimental study of teaching Arabic as a second language in Malaysia - Hj. Yaakub, Muhamadul Bakir; Abd. Razak, Rafidah (2010)
The success of a second language teaching and learning is one of the central topics in cognitive science. Theories of cognition had tried to explain it; probably no other topic has aroused such controversy. Generally, commentators have focused on the technical difficulties of working with a second language such as grammatical rules and pronunciation. However, the technical aspects of a language are just a matter of absolving a natural phenomenon. The real problem here came from the stereotypes of dealing methodologies and it should be evaluated before a comparison can be made. This step is a principal responsibility of every teacher who strives to use their observations and evaluations to improve their teaching effectiveness and always look forward to learn, develop or apply new research-based teaching practices within their teaching methods. In the case of learning Arabic, memorization can be assumed to be a difficult task to Malay learners. For this reason, this study was tried to evaluate the effectiveness and practicalities of the “Key-word method” in improving the betterment of both teachers and learners performance and the ability enhancement in overcoming the challenges, so that they become motivated in achieving their learning target and become innovative in their learning activities.